ANALISIS PERBEDAAN MOTIVASI KERJA DAN KINERJA GURU PADA GURU YANG BERSERTIFIKAT DAN TIDAK BERSERTIFIKAT DI SMA NEGERI 1 DAN 2 NUBATUKAN KABUPATEN LEMBATA - Cristiyani Katharina Niga Wawin; Catharina Wigati Retno Astuti (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
The objectives of this study were to examine and analyze whether there were differences in work motivation and teacher performance between certified and uncertified teachers in SMA Negeri 1 and 2 Nubatukan, Lembata District. The research was conducted in January 2021. This study is a comparative research. The research population were teachers of SMA Negeri 1 and SMA Negeri 2 Nubatukan, Lembata District. The number of sample was 82 teachers. The research sampling technique was saturated sampling technique. The data collection technique was a questionnaire. The data analysis technique was Man Whitney test. The results of data analysis showed that: (1) there were differences of work motivation between certified and non-certified teachers in SMA Negeri 1 and 2 Nubatukan, Lembata District and (2) there were differences of teacher performance between certified and non-certified teachers in SMA Negeri 1 and 2 Nubatukan, Lembata District.Keywords: work motivation, teacher performance, certified teachers, non-certified teachers